2008
DOI: 10.1080/00952990802308197
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Period1 Gene Attenuates the Morphine-Induced ERK-CREB Activation in Frontal Cortex, Hippocampus, and Striatum in Mice

Abstract: Our results indicated that per1 plays an important role in morphine reward, and ERK-CREB pathway was involved in the effects of per1. We suggested that per1 gene may be a potential treatment target for drug addition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
3
5
0
Order By: Relevance
“…These changes are in good agreement with current models indicating that Rev-erba acts as a potent repressor of Cry1 expression and that Cry1 works as a negative regulator of Per1 expression (Etchegaray et al, 2003). The potential behavioral relevance of these changes in Per1 expression is highlighted by studies showing that both mice and Drosophila mutants, lacking, respectively, Per1 or Per, failed to show sensitization to cocaine (Abarca et al, 2002;Andretic et al, 1999), and the reduction of Per1 activity in mice by DNAzyme led to a reduction in CPP for morphine (Li et al, 2008). The mechanisms by which circadian clock genes regulate addictive behavior remain elusive (Perreau-Lenz et al, 2007), but probably involve their regulatory function on dopamine receptor responsiveness (Andretic and Hirsh, 2000).…”
Section: Discussionsupporting
confidence: 64%
“…These changes are in good agreement with current models indicating that Rev-erba acts as a potent repressor of Cry1 expression and that Cry1 works as a negative regulator of Per1 expression (Etchegaray et al, 2003). The potential behavioral relevance of these changes in Per1 expression is highlighted by studies showing that both mice and Drosophila mutants, lacking, respectively, Per1 or Per, failed to show sensitization to cocaine (Abarca et al, 2002;Andretic et al, 1999), and the reduction of Per1 activity in mice by DNAzyme led to a reduction in CPP for morphine (Li et al, 2008). The mechanisms by which circadian clock genes regulate addictive behavior remain elusive (Perreau-Lenz et al, 2007), but probably involve their regulatory function on dopamine receptor responsiveness (Andretic and Hirsh, 2000).…”
Section: Discussionsupporting
confidence: 64%
“…We found that chronic morphine exposure increased p-ERK and p-CREB expression in the vHip and mPFC following D1R activation. These results are consistent with a previous study [29]. Our previous study has revealed that these protein levels in Hip are positively correlated with D1R activation during memory processes [24].…”
Section: Discussionsupporting
confidence: 94%
“…Interestingly, the results of our study demonstrated that ERK1/2 and CREB protein levels in hippocampus are not changed, rather pERK1/2 and pCREB protein levels in the hippocampus are up-regulated markedly in both the acquisition and maintenance of morphine conditioned place preference memory. These results are consistent with prior reports that the ERK-CREB pathway is involved in chronic morphine associated memory 38 39 , especially in the mechanism for the reconsolidation of drug addiction memory 40 .…”
Section: Discussionsupporting
confidence: 93%